ISLAMISASI ILMU PENGETAHUAN (EKSAKTA) DALAM MENGATASI TANTANGAN ERA MILENIAL - Anggi Yusriana; Ardi Ardi; Rahmawati Rahmawati; Nadiyah Farhah Salsabila (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2023)
The Islamization of science is the answer to the condition of Muslims who are left behind by the West. The concept of Islamization of science implicitly illustrates the anxiety of Muslim scholars in seeing the development of modern Western science which is dry of religious values. Islam strongly encourages its people to seek knowledge. Even Allah SWT. has promised to increase the degree of someone who is knowledgeable. The Islamization of science is a synthesis of modern science that denies religious and secular values ​​with Islam which is too exalted and presents a whole and integral new science without any dichotomy between the two. The dim science in the Islamic world, the West is actually experiencing a very rapid development of science. The purpose of this literature review is to find out how the Islamization of science is in facing the challenges of the millennial era. The method used in this study is a literature review by analyzing as many as 8 articles that are relevant to the topic. From the analysis of the article, it is stated that the process of Islamization of science is very necessary because the development of Western science deviates from Islamic teachings or can be said to have had a bad impact. Especially in this millennial era, the influence of globalization and Westernization has forced Muslims to adapt. The implication of the results of this study is that the Islamization of knowledge can have a positive impact on Muslims.